JENIS MINERAL DAN SIFAT KIMIA TANAH VERTISOL HASIL PELAPUKAN BATUAN GAMPING DI KABUPATEN JENEPONTO - masria ria masria (Partner, 2019)
This study aims to study the types of minerals and chemical properties of Vertisol soil that develop from limestone rocks in Jeneponto Regency, South Sulawesi. Taking soil samples is carried out at four different depths, namely: 0-15 cm, 15-30 cm, 30-45 cm,  and 45-60 cm. Observation parameters for soil mineral types are primary minerals and secondary minerals, while soil chemical properties observed are pH, C-organic, cation exchange capacity (CEC). The results showed that the dominant primary mineral species were calcite and quartz, the dominant secondary mineral species was montmorillonite. Soil chemistry for soil pH ranges from 6.58-6.85, C-organic ranges from 2.23-2.81% or moderate status, and CEC ranges from 19.98 to 22.76 cmol (+) / kg or moderate status.